Design of Application for Reporting Violence Against Women and Children in RT.001 RW.005 KEL.Dukuh with Waterfall Method - Sopian, Abu; Setiadi, Dedi (Universitas Mohammad Husni Thamrin, 2025)
Violence against women and children is a violation of human rights that occurs across various layers of society, with a significant increase in Indonesia. Data shows that the number of cases of violence against women and children in East Jakarta reached 302 cases in the first six months of 2024. RT.001 RW.005 in the Dukuh Kramat Jati area is one of the areas facing this issue. In this context, incidents of violence are often not addressed or reported swiftly, leading to victims not receiving the protection they deserve. This study aims to design the